If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(u+3)=2u-4+2(4u+6)
We move all terms to the left:
-2(u+3)-(2u-4+2(4u+6))=0
We multiply parentheses
-2u-(2u-4+2(4u+6))-6=0
We calculate terms in parentheses: -(2u-4+2(4u+6)), so:We get rid of parentheses
2u-4+2(4u+6)
determiningTheFunctionDomain 2u+2(4u+6)-4
We multiply parentheses
2u+8u+12-4
We add all the numbers together, and all the variables
10u+8
Back to the equation:
-(10u+8)
-2u-10u-8-6=0
We add all the numbers together, and all the variables
-12u-14=0
We move all terms containing u to the left, all other terms to the right
-12u=14
u=14/-12
u=-1+1/6
| -0.5(2x+8)-(-3x)=77 | | 3y-7=12-y+13 | | 8x-4=7-3x | | (b-91)/6=1 | | –5x–11=8x+15 | | 2(x-3)-1=5x-4 | | u+3-6u=7-49 | | 400=-9+4n | | 15(6x)=33 | | a-23=123 | | 29+8d=85 | | 3x-8+120=13x-8 | | 8=c3+ 4 | | Y=-3.5x+8 | | -2.5x=-45 | | b12=11 | | 5z+7=3-z-14 | | 728=b-2437 | | 18=x/4-2 | | 15X6x=33 | | 9(x-8)=-2x-28 | | (x-54)+x=796 | | 1+n/5=-3 | | 7-2x=42+4x-5 | | 2(3y+16)-6y=32 | | 3x-9+50=11+6x | | 15w=450 | | (h+34)/10=6 | | 24=a/3 | | 8+4t=5-3t-25 | | 2x-4(2x-1)+7=3-4x | | 18/25=126/y |